High-transparency high-temperature-resistant cooling heat-dissipation energy-saving self-cleaning film as well as preparation method and application thereof

By using a high-transparent high-temperature cooling and cooling energy-saving self-cleaning film with a combination of modified nanoparticles and functional additives in transportation, electronic products and industrial fields, the problem of insufficient heat dissipation and cleaning functions in the prior art is solved, and efficient Self-cleaning and thermal conductivity meet diverse performance needs and reduce costs.

CN119220139AInactive Publication Date: 2024-12-31GUANGDONG YIZHI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411521007.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has problems such as high energy consumption, high cost, insufficient self-cleaning function and unbalanced performance in the heat dissipation and cleaning of equipment in transportation, electronic products and industrial fields, and cannot achieve high transparency, high temperature resistance, cooling and self-cleaning effects.

Method used

High-transparent high-temperature cooling and heat-saving self-cleaning film made of high-quality resin materials, improves the mechanical and mechanical properties of the film layer, waterproof, aging resistance and antistatic properties, and combines nanometers. Nanomaterials such as silver and nanographene achieve self-cleaning and thermal conductivity.

Benefits of technology

It has achieved excellent high-temperature baking, cooling and heat dissipation, and self-cleaning performance, while maintaining excellent waterproof, aging resistance and anti-static properties, meeting diverse needs, extending service life, reducing usage costs, and having excellent application prospects. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the field of film materials, in particular to a high-transparency high-temperature-resistant cooling heat-dissipation energy-saving self-cleaning film and a preparation method and application thereof. The high-transparency high-temperature-resistant energy-saving self-cleaning film is prepared from the following raw materials in parts by mass: 15 to 45 parts of basic emulsion, 25 to 65 parts of nano particles, 10 to 20 parts of functional additive, 20 to 30 parts of diluent, 2 to 3 parts of silicone oil, 1 to 3 parts of flatting agent, 2 to 5 parts of wetting agent and 1 to 3 parts of dispersing agent. The high-transparency, high-temperature-resistant, cooling, heat-dissipating, energy-saving and self-cleaning film prepared by the invention can maintain excellent high-temperature baking resistance, cooling, heat-dissipating, self-cleaning performance and mechanical properties, and also has good waterproof, aging-resistant, corrosion-resistant, antistatic and other performances; the high-transparency, high-temperature-resistant, cooling, heat-dissipating, energy-saving and self-cleaning film provided by the invention meets the diversified performance requirements of the existing traffic tool field, electronic product field, industrial field and civil field on the high-transparency, high-temperature-resistant, cooling, heat-dissipating and energy-saving self-cleaning film, realizes better comprehensive performance and long service life, has a good energy-saving effect, reduces the use cost, and has a very excellent application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of membrane materials, and in particular to a highly transparent, high-temperature-resistant, cooling, heat-dissipating, energy-saving and self-cleaning membrane, and a preparation method and application thereof. Background Art

[0002] At present, the heat dissipation of equipment, facilities and appliances in the fields of transportation, electronic products, industry and civil fields is basically achieved through air conditioning cooling, air cooling, water cooling and other methods, which cannot achieve self-cooling and heat dissipation, consume a lot of energy and have high cost of use; the cleaning of equipment, facilities and appliances in the fields of transportation, electronic products, industry and civil fields is basically achieved through water washing, insulation material cleaning, electric wind dry cleaning and other methods, which cannot achieve self-cleaning treatment and transparent protection and new use effects. However, with the development of science and technology and people's higher requirements for the performance of equipment, facilities, appliances and other products in the fields of transportation, electronic products, industry and civil fields, the emerging technical direction of high-transparency, high-temperature-resistant, cooling, heat-dissipating and energy-saving self-cleaning films has gradually come into people's view.

[0003] Highly transparent, high temperature resistant, cooling, heat dissipation, energy-saving and self-cleaning film is a high-performance protective film, usually made of high-quality resin materials. Its main function is to provide additional functions without affecting the appearance of vehicles, equipment, facilities and appliances in the fields of transportation, electronic products, industry and civil fields: cooling and heat dissipation, self-cleaning as new, refracting ultraviolet infrared rays, and improving the high-temperature protection layer on the outside of high-heat energy objects to prevent damage from acid rain and other environmental factors. The characteristics of highly transparent, high temperature resistant, cooling, heat dissipation and energy-saving self-cleaning film mean that this film layer has good heat dissipation and cooling functions for heat sources, and has a certain ability to reduce the adhesion of dirt, dust and other pollutants, or make these pollutants easier to wash off, which is usually due to special treatment or coating on the surface of the film. But at the same time, the existing self-cleaning functional materials still have uneven performance or lack of performance in terms of new properties such as waterproof, antistatic, aging resistance, corrosion resistance and mechanical mechanical properties.

[0004] Therefore, in order to solve the above problems, the present application provides a highly transparent, high-temperature resistant, cooling, heat dissipation, energy-saving and self-cleaning film and a preparation method thereof. The highly transparent, high-temperature resistant, cooling, heat dissipation, energy-saving and self-cleaning film prepared in the present application can maintain excellent high-temperature baking resistance, cooling and heat dissipation, self-cleaning performance and mechanical properties, while maintaining good waterproof, aging resistance, corrosion resistance and anti-static properties, meeting the diverse performance requirements of the existing transportation, electronic products, industrial and civil fields for highly transparent, high-temperature resistant, cooling, heat dissipation, energy-saving and self-cleaning films, achieving good comprehensive performance and long service life, while having good energy-saving effects, reducing the cost of use, and having very excellent application prospects. Summary of the invention

[0005] In order to solve the above problems, the first aspect of the present application provides a highly transparent, high-temperature resistant, cooling, heat dissipation, energy-saving and self-cleaning film. The raw materials are, by mass: 15 to 45 parts of base emulsion, 25 to 65 parts of nanoparticles, 10 to 20 parts of functional additives, 20 to 30 parts of diluents, 2 to 3 parts of silicone oil, 1 to 3 parts of leveling agents, 2 to 5 parts of wetting agents, and 1 to 3 parts of dispersants.

[0006] As a preferred solution, the mass ratio of the base emulsion, the nanoparticles and the functional additive is (25-38): (35-45): (12-18).

[0007] As a preferred solution, the mass ratio of the base emulsion, the nanoparticles and the functional additive is (30-36): (38-42): (14-16).

[0008] As a preferred solution, the mass ratio of the base emulsion, the diluent and the silicone oil is (25-38): (22-26): (2-3).

[0009] As a preferred solution, the mass ratio of the base emulsion, the diluent and the silicone oil is (30-36): (24-25): (2-3).

[0010] As a preferred solution, the base emulsion is a composition of modified acrylic emulsion, polyvinyl methyl ether and fluorocarbon emulsion.

[0011] As a preferred solution, the mass ratio of the modified acrylic emulsion to polyvinyl methyl ether and fluorocarbon emulsion is (2-3): (0.5-1.2): (0.5-1.2).

[0012] As a preferred solution, the mass ratio of the acrylic emulsion to polyvinyl methyl ether and fluorocarbon emulsion is (2.2-2.5): (0.5-1.2): (0.8-1).

[0013] As a preferred solution, the viscosity of the modified acrylic emulsion is 150-300 mPa·s at 25°C.

[0014] As a preferred solution, the solid content of the modified acrylic emulsion is 50-55 wt %.

[0015] As a preferred solution, the fluorine content of the fluorocarbon emulsion is 10-15wt%.

[0016] As a preferred solution, the solid content of the fluorocarbon emulsion is 40-48wt%.

[0017] As a preferred solution, the nanoparticles are a composite of modified organic silicon nanosilver, nanographene, nanocerium sulfate, nanozirconium oxide, nanoaluminum oxide, nanozinc oxide, nanosilicon carbide and nanotitanium dioxide.

[0018] As a preferred solution, the nanoparticles are modified organic silicon nanosilver, nanographene, nanocerium sulfate, nanozirconium oxide, nanoaluminum oxide, nanozinc oxide, nanosilicon carbide, and nanotitanium dioxide in a mass ratio of (2-2.5): (0.1-18) (2-2.5): (1-1.4): (1-1.4): (1-1.4); (1-1.4): (1-1.4);

[0019] As a preferred solution, the average particle size of the modified organosilicon nanosilver is 10 to 20 nm.

[0020] As a preferred solution, the average particle size of the nanographene is 10 to 20 nm.

[0021] As a preferred solution, the average particle size of the nano zirconium oxide is 10 to 20 nm.

[0022] As a preferred solution, the average particle size of the rice alumina is 10 to 20 nm.

[0023] As a preferred solution, the average particle size of the nano zinc oxide is 10 to 20 nm.

[0024] As a preferred solution, the average particle size of the nano-silicon carbide is 10 to 20 nm.

[0025] As a preferred solution, the average particle size of the nano titanium dioxide is 10 to 20 nm.

[0026] As a preferred solution, the preparation method of the modified organosilicon nanosilver comprises the following steps: S1: adding nanosilver to a mixed solvent of ethanol and isobutanol, uniformly dispersing by ultrasonication at 200-250W, adjusting the pH value to 9-10 with triethanolamine, then adding tetraethyl orthosilicate, isopropanol, silane coupling agent and polysiloxane, heating to 65-70°C and keeping the temperature for reaction for 2.5-3h, and after the reaction is completed, centrifuging and filtering the product, washing with ethanol and drying to obtain the modified organosilicon nanosilver.

[0027] The mass ratio of the modified organic silicon nanosilver, orthosilicic acid, ethyl isopropyl alcohol, silane coupling agent and polysiloxane is (3.5-3.8): (0.8-0.9): (0.2-0.25): (0.08-0.12): (0.5-1);

[0028] As a preferred solution, the mass ratio of the modified organic silicon nanosilver, tetraethyl orthosilicate, isopropyl alcohol and silane coupling agent is (3.5-3.8): (0.8-0.9): (0.2-0.25): (0.08-0.12).

[0029] As a preferred solution, the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.

[0030] As a preferred solution, the mass ratio of the pretreated modified organosilicon nanosilver, sodium dodecylbenzene sulfonate, succinic anhydride and hydrofluoric acid is (4-4.5): (0.3-0.4): (1.5-1.8): (10-12).

[0031] As a preferred solution, the average particle size of the modified organosilicon nanosilver is 15 to 25 nm.

[0032] The combination of modified organosilicon nano-silver oxide and nano-graphene, nano-cerium sulfate, nano-zirconium oxide, and nano-iron oxide added in this application can effectively improve the mechanical properties, aging corrosion resistance, and waterproof and moisture-proof properties of the highly transparent, high-temperature resistant, cooling and heat dissipating self-cleaning film, thereby maintaining good film cleanliness. The modified organosilicon nano-silver has enhanced stability: the introduction of organosilicon can significantly enhance the stability of nano-silver particles, prevent them from agglomerating or precipitating, and thus maintain their uniform dispersion in the solution. The modified nano-silver particles have better antibacterial, electrical, thermal, catalytic, and sunlight refraction properties. The modified organic silicon nano-silver oxygen is used together to achieve the ultimate thermal conductivity and heat dissipation performance. The nano material requires high transparency, and high transparency can improve the radiation performance of the heat source; nano-graphene has greatly improved the aging and corrosion resistance; polyvinyl methyl ether and fluorocarbon emulsion can improve hydrophobicity and surface smoothness; the modified organic silicon nano-silver oxygen is used together with nano-cerium sulfate, nano-zirconia, nano-zirconia, nano-aluminum oxide, nano-zinc oxide, nano-silicon carbide, and nano-titanium dioxide to make the film have good thermal conductivity, antistatic properties and antibacterial functions. Nano-aluminum oxide, nano-zinc oxide, nano-silicon carbide, and nano-titanium dioxide have reflection and refraction effects on sunlight through light sources, infrared rays, and ultraviolet rays. Most of the heat radiated by sunlight is reflected and refracted.

[0033] As a preferred solution, the functional auxiliary agent is a composition of polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether.

[0034] As a preferred solution, the mass ratio of the polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether is (4-5): (3-3.5): (1-2).

[0035] As a preferred solution, the weight average molecular weight of the polyethylene glycol methyl ether is 400 to 800 Da.

[0036] As a preferred solution, the weight average molecular weight of the epoxy block polyether is 6000-8000 Da.

[0037] As a preferred solution, the ethylene oxide block content of the epoxy block polyether is 60 to 70 wt%.

[0038] As a preferred solution, the aromatic phenol polyoxyethylene ether is a combination of phenethylphenol polyoxyethylene ether and trimethylstyrenephenol polyoxyethylene ether.

[0039] As a preferred solution, the mass ratio of the phenethylphenol polyoxyethylene ether to the trimethylstyrenephenol polyoxyethylene ether is (3-4): (0.6-0.8).

[0040] As a preferred solution, the HLB value of the phenethylphenol polyoxyethylene ether is 10-12.

[0041] As a preferred solution, the HLB value of the trimethylstyrene phenol polyoxyethylene ether is 15-18.

[0042] The above-mentioned composite functional additives added in the present application can effectively assist in improving the mechanical properties of the film layer, and can effectively guarantee the waterproof and aging corrosion resistance. The epoxy block polyether and polyethylene glycol methyl ether added in the present application can enhance the molecular network construction assistance effect of the overall functional additives in the film material by embedding the effect of different molecular chain lengths, thereby enhancing the tightness of the internal three-dimensional network of the film layer, and molecular chains of different lengths are easy to form entanglements with each other, which helps to improve the intermolecular force, thereby assisting in improving the mechanical properties of the film layer, and the addition of arylphenol polyoxyethylene ether can effectively reduce the agglomeration of each nanoparticle added in the present application, so that the epoxy block polyether and polyethylene glycol methyl ether are better used as dispersion carriers in the formation of the film layer, thereby enhancing the uniformity of each particle in the film layer, and can avoid the formation of large particle micropores caused by particle agglomeration, thereby affecting the connection between molecules and particles, and finally reducing the friction mechanical properties. On the other hand, the compounded functional additives can also assist in the formation of a smooth film surface of fluorocarbon resin and polyvinyl methyl ether on the surface, thereby improving the overall waterproof and aging corrosion resistance of the film layer.

[0043] As a preferred solution, the diluent is at least one of ethanol, methanol, isopropanol or ethyl acetate.

[0044] As a preferred solution, the leveling agent is at least one of organic silicon leveling agents.

[0045] As a preferred solution, the wetting agent is at least one of non-ionic wetting agents.

[0046] As a preferred solution, the dispersant is at least one of polyurethane, acrylic acid, and silicone acrylic.

[0047] The second aspect of the present application provides a method for preparing a highly transparent, high-temperature resistant, cooling, heat dissipating, energy-saving and self-cleaning film, and the specific steps include the following steps: S1: Add diluent, functional additives, silicone oil, and base emulsion into a high-speed mixer, and stir at 1200-1800 rpm for 10-20 minutes until uniform; S2: After adding the nanoparticles, continue to maintain a speed of 1200-1800 rpm and stir for 15-25 minutes; S3: Finally, add a leveling agent, a wetting agent and a dispersant at a speed of 800-1000 rpm, stir for 8-10 minutes, and after completion, coat the mixture on the desired substrate surface, heat to 60-80°C and cure for 4-6 hours or self-dry and cure for 24 hours; the result is obtained.

[0048] The second aspect of the present application provides a kind of above-mentioned high-transparency, high-temperature-resistant, cooling, heat-dissipating, energy-saving and self-cleaning film, which meets the diverse performance requirements of the transportation, electronic products, industrial and civil fields for high-transparency, high-temperature-resistant, cooling, heat-dissipating, energy-saving and self-cleaning film, achieves good comprehensive performance and long service life, and at the same time has good energy-saving effect, reduces the cost of use, and has very excellent application prospects.

[0049] The beneficial effects of this application are:

[0050] 1. The present application provides a highly transparent, high-temperature resistant, cooling, heat dissipation, energy-saving and self-cleaning film, which can maintain excellent high-temperature baking resistance, cooling and heat dissipation, energy saving and emission reduction, self-cleaning performance and mechanical properties while maintaining good waterproof, aging resistance, corrosion resistance and anti-static properties. It meets the diverse performance requirements of the existing transportation, electronic products, industrial and civil fields for highly transparent, high-temperature resistant, cooling, heat dissipation, energy-saving and self-cleaning films, achieves good comprehensive performance and long service life, reduces the cost of use, and has very excellent application prospects.

[0051] 2. A highly transparent, high-temperature-resistant, cooling, heat-dissipating, energy-saving, self-cleaning film provided in this application has enhanced stability after the addition of modified organosilicon nanosilver: the introduction of organosilicon can significantly enhance the stability of nanosilver particles, prevent them from agglomerating or precipitating, and thus maintain their uniform dispersion in the solution. The modified nanosilver particles have better antibacterial, conductive, thermally conductive, catalytic, and sunlight refraction properties. The use of modified organosilicon nanosilver oxide together allows the thermal conductivity and heat dissipation performance to reach the extreme. The nano requirements of the material can achieve the purpose of high transparency, and high transparency can improve the radiation performance of the heat source; nanographene has a significant improvement in aging and corrosion resistance; polyvinyl methyl ether and fluorocarbon emulsion can improve hydrophobicity and surface smoothness; modified organosilicon nanosilver oxide is used together with nano cerium sulfate, nano zirconium oxide, nano aluminum oxide, nano zinc oxide, nano silicon carbide, and nano titanium dioxide to give the film layer good thermal conductivity, antistatic properties, and antibacterial functions. Nano-aluminum oxide, nano-zinc oxide, nano-silicon carbide, and nano-titanium dioxide have the effects of reflecting and refracting sunlight, infrared rays, and ultraviolet rays. Most of the heat radiated by sunlight is reflected and refracted.

[0052] 3. The core principle of the self-cleaning function of the modified organic silicon nanosilver added in the present application is to introduce nanosilver particles on the surface of the material and use its excellent antibacterial properties and unique surface properties to achieve a self-cleaning effect. This material can not only effectively inhibit bacterial growth, but also prevent the adhesion of dirt and grease, thereby keeping the surface clean and hygienic.

[0053] 4. A highly transparent, high temperature resistant, cooling, heat dissipation and energy-saving self-cleaning film provided in the present application, the added composite functional additive can effectively assist in improving the mechanical properties of the film layer, and can effectively ensure the waterproof and aging corrosion resistance of the self-cleaning film. Epoxy block polyether and polyethylene glycol methyl ether can enhance the molecular network construction assistance effect of the overall functional additive in the film material by embedding the effect of different molecular chain lengths, thereby enhancing the tightness of the internal three-dimensional network of the film layer, and molecular chains of different lengths can easily form entanglements with each other, which helps to improve the intermolecular force, thereby helping to improve the mechanical properties of the film layer, and the addition of aromatic phenol polyoxyethylene ether can effectively reduce the agglomeration of each nanoparticle added in the present application, so that epoxy block polyether and polyethylene glycol methyl ether can be better used as dispersion carriers in the formation of the film layer, thereby enhancing the uniformity of each particle in the film layer, and can avoid the formation of large particle micropores caused by particle agglomeration, thereby affecting the connection between molecules and particles, and finally reducing the friction mechanical properties. DETAILED DESCRIPTION

[0054] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0055] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0056] Example 1

[0057] Example 1 The first aspect provides a highly transparent, high-temperature resistant, cooling, heat dissipation, energy-saving and self-cleaning film. The raw materials are, by mass: 34.6 parts of base emulsion, 39.5 parts of nanoparticles, 15.5 parts of functional additives, 24.8 parts of diluents, 3 parts of silicone oil, 2.2 parts of leveling agents, 3.8 parts of wetting agents, and 2.5 parts of dispersants.

[0058] The basic emulsion is a composition of modified acrylic emulsion, polyvinyl methyl ether and fluorocarbon emulsion, and the mass ratio of the three is 2.4:1:1.

[0059] The modified acrylic emulsion is an organic siloxane modified acrylic emulsion with a viscosity of 240 mPa·s, a solid content of 52.2 wt % at 25°C,

[0060] The fluorine content of the fluorocarbon emulsion is 11.6wt%, the solid content is 46.5wt%,

[0061] The nanoparticles are modified organic silicon nanosilver, nanographene, nanocerium sulfate, nanozirconium oxide, nanoaluminum oxide, nanozinc oxide, nanosilicon carbide, and nanotitanium dioxide, and the mass ratio of the composite is (2-2.5): (0.1-18) (2-2.5): (1-1.4): (1-1.4): (1-1.4); (1-1.4): (1-1.4);

[0062] The preparation method of the modified nano silver comprises the following steps: S1: adding nano silver to a mixed solvent of ethanol and isobutanol, uniformly dispersing by ultrasonication at 200-250W, adjusting the pH value to 9-10 with triethanolamine, then adding tetraethyl orthosilicate, isopropanol, silane coupling agent and polysiloxane, heating to 65-70°C for reaction for 2.5-3h, centrifuging and filtering the product after the reaction is completed, washing with ethanol and drying to obtain modified organosilicon nano silver.

[0063] The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.

[0064] The functional additive is a composition of polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether, and the mass ratio of the three is 4.3:3.2:1.4.

[0065] The weight average molecular weight of polyethylene glycol methyl ether is 400Da.

[0066] The weight average molecular weight of the epoxy block polyether is 7800Da, and the ethylene oxide block content is 70wt%.

[0067] The aromatic phenol polyoxyethylene ether is a composition of phenylethylphenol polyoxyethylene ether and trimethylstyrenephenol polyoxyethylene ether, and the mass ratio of the two is 3.6:0.8.

[0068] The HLB value of phenethylphenol polyoxyethylene ether is 11, and the HLB value of trimethylstyrenephenol polyoxyethylene ether is 16.

[0069] The diluent is 95wt% ethanol; the leveling agent is organic silicone leveling agent BYK-306.

[0070] The wetting agent is a nonionic wetting agent and the dispersing agent is acrylic BYK-163.

[0071] The second aspect of the present embodiment provides a method for preparing a highly transparent, high-temperature resistant, cooling, heat dissipating, energy-saving and self-cleaning film, and the specific steps include the following steps: S1: Add diluent, functional additives, silicone oil, and base emulsion into a high-speed mixer, and stir at 1500rpm for 15 minutes until uniform; S2: After adding the nanoparticles, continue to maintain a speed of 1500rpm and stir for 20 minutes; S3: Finally, add a leveling agent, a wetting agent and a dispersant at a speed of 1000rpm, stir for 9 minutes, and after completion, apply the mixture on the desired substrate surface, heat to 70°C and cure for 5.5 hours or self-dry and cure for 24 hours.

[0072] Example 2

[0073] The first aspect of Example 2 provides a highly transparent, high-temperature resistant, cooling, heat dissipation, energy-saving and self-cleaning film. The raw materials, in parts by mass, are: 30.5 parts of base emulsion, 35.6 parts of nanoparticles, 14.2 parts of functional additives, 24.8 parts of diluents, 3 parts of silicone oil, 2.2 parts of leveling agents, 3.8 parts of wetting agents, and 2.5 parts of dispersants.

[0074] The base emulsion is a composition of modified acrylic acid emulsion, polyvinyl methyl ether and fluorocarbon emulsion, and the mass ratio of the three is 2.2:1.2:1.2.

[0075] The modified acrylic emulsion is an organic siloxane modified acrylic emulsion with a viscosity of 240 mPa·s, a solid content of 52.2 wt % at 25°C,

[0076] The fluorine content of the fluorocarbon emulsion is 11.6wt%, the solid content is 46.5wt%,

[0077] The nanoparticles are modified organic silicon nanosilver, nanographene, nanocerium sulfate, nanozirconium oxide, nanoaluminum oxide, nanozinc oxide, nanosilicon carbide, and nanotitanium dioxide in a mass ratio of (2-2.5): (0.1-18) (2-2.5): (1-1.4): (1-1.4): (1-1.4); (1-1.4): (1-1.4);

[0078] The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.

[0079] The preparation method of modified organic silicon nanosilver comprises the following steps: S1: adding nanosilver to a mixed solvent of ethanol and isobutyl alcohol, uniformly dispersing by ultrasonication at 200-250W, adjusting the pH value to 9-10 with triethanolamine, then adding tetraethyl orthosilicate, isopropyl alcohol, silane coupling agent and polysiloxane, heating to 65-70°C for reaction for 2.5-3h, centrifuging and filtering the product after the reaction is completed, washing with ethanol and drying to obtain modified organic silicon nanosilver.

[0080] The average particle size of the modified organosilicon nanosilver is 20-25 nm.

[0081] The functional additive is a composition of polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether, and the mass ratio of the three is 4.3:3.2:1.4.

[0082] The weight average molecular weight of polyethylene glycol methyl ether is 400Da.

[0083] The weight average molecular weight of the epoxy block polyether is 7800 Da, the ethylene oxide block content is 70 wt %, and the product is an ethylene oxide-propylene oxide block copolyether product of model L87 purchased from BASF.

[0084] The aromatic phenol polyoxyethylene ether is a composition of phenylethylphenol polyoxyethylene ether and trimethylstyrenephenol polyoxyethylene ether, and the mass ratio of the two is 3.6:0.8.

[0085] The HLB value of phenethylphenol polyoxyethylene ether is 11; the HLB value of trimethylstyrenephenol polyoxyethylene ether is 16.

[0086] The diluent is 95wt% ethanol; the leveling agent is organic silicone leveling agent BYK-306.

[0087] The wetting agent is a nonionic wetting agent; the dispersing agent is acrylic BYK-163.

[0088] The second aspect of the present embodiment provides a method for preparing the above-mentioned highly transparent, high-temperature resistant, cooling, heat dissipation, energy-saving and self-cleaning film, and the specific steps include the following steps: S1: Add diluent, functional additives, silicone oil, and basic emulsion into a high-speed mixer, and stir at 1500rpm for 15 minutes until uniform; S2: After adding the nanoparticles, continue to maintain a speed of 1500rpm and stir for 20 minutes; S3: Finally, add leveling agent, wetting agent and dispersant at a speed of 1000rpm, stir for 9 minutes, and after completion, apply the mixture on the desired substrate surface, heat to 70°C and cure for 5.5 hours, or dry cure for 24 hours to obtain the mixture.

[0089] Comparative Example 1

[0090] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being: a highly transparent, high-temperature-resistant, cooling, heat-dissipating, energy-saving and self-cleaning film, wherein the raw materials are, by mass: 46.8 parts of base emulsion, 25.8 parts of nanoparticles, 15.5 parts of functional additives, 24.8 parts of diluents, 3 parts of silicone oils, 2.2 parts of leveling agents, 3.8 parts of wetting agents and 2.5 parts of dispersants.

[0091] Comparative Example 2

[0092] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being: a highly transparent, high-temperature-resistant, cooling, heat-dissipating, energy-saving and self-cleaning film, wherein the raw materials, by mass, are: 40.6 parts of base emulsion, 39.5 parts of nanoparticles, 5.6 parts of functional additives, 24.8 parts of diluent, 3 parts of silicone oil, 2.2 parts of leveling agent, 3.8 parts of wetting agent, and 2.5 parts of dispersant.

[0093] Comparative Example 3

[0094] The specific implementation of this comparative example is basically the same as that of Example 1, except that the mass ratio of the modified silicone acrylic emulsion to the fluorocarbon emulsion is 4:0.6.

[0095] Comparative Example 4

[0096] The specific implementation of this comparative example is basically the same as that of Example 1, except that the mass ratio of the nanoparticles is (2-2.5): (0.1-18) (2-2.5): (1-1.4): (1-1.4): (1-1.4); (1-1.4): (1-1.4); (1-1.4): (1-1.4);

[0097] Comparative Example 5

[0098] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the azoles are mixed and stirred, kept warm for 2 hours, and after completion, the product is centrifuged and filtered, washed with ethanol for 3 times, and then vacuum dried to obtain the product.

[0099] Comparative Example 6

[0100] The preparation method of the modified nano silver comprises the following steps: adding the nano silver into a mixed solvent of ethanol and isobutanol, uniformly dispersing the nano silver by ultrasonication at 200-250W, adjusting the pH value to 9-10 by triethanolamine, then adding tetraethyl orthosilicate, isopropanol, silane coupling agent and polysiloxane, heating to 65-70°C for heat preservation and reaction for 2.5-3h, centrifuging and filtering the product after the reaction is completed, washing with ethanol and drying to obtain the modified organosilicon nano silver.

[0102] Comparative Example 7

[0103] The specific implementation of this comparative example is basically the same as that of Example 1, except that the functional additive is a composition of polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether, and the mass ratio of the three is 8:2:0.3.

[0104] Comparative Example 8

[0105] The specific implementation of this comparative example is basically the same as that of Example 1, except that the weight average molecular weight of the epoxy block polyether is 1600 Da, the ethylene oxide block content is 20 wt %, and the L42 ethylene oxide-propylene oxide block copolyether product is purchased from BASF.

[0106] Performance Evaluation

[0107] 1. Mechanical properties: For the preparation method of a highly transparent, high-temperature resistant, cooling, heat dissipation, energy-saving and self-cleaning film obtained in the embodiment and the comparative example, a sample with a thickness of 0.2 mm, a length of 2 cm and a width of 1 cm was taken, and the tensile strength and elongation at break were tested using a universal stretching machine. The test values ​​were taken as the average value of 10 tests and recorded in Table 1.

[0108] 2. Cooling and heat dissipation performance: Samples with a thickness of 0.2 mm, a length of 2 cm, and a width of 1 cm were taken from the transparent high-temperature cooling, heat dissipation, energy-saving self-cleaning films prepared in the embodiments and comparative examples, and placed in an outdoor environment for 6 months in a fixed test group. The average environmental range was 26.8-28.2°C, and the average relative humidity range was 66.4-70.1%. After 6 months, the samples were taken back and naturally rinsed with clean water. The surface of the transparent high-temperature cooling, heat dissipation, self-cleaning film sample segments were randomly intercepted to detect the percentage of dirt occupying the area. The test values ​​were taken as the average of 10 tests and recorded in Table 1.

[0109] 3. Waterproof performance: For the preparation method of a highly transparent, high-temperature resistant, cooling, heat dissipation, energy-saving and self-cleaning film obtained in the embodiment and the comparative example, a sample with a thickness of 0.2 mm, a length of 2 cm and a width of 1 cm was taken, and the water contact angle on the surface of the film layer was tested by the sessile drop method. The test water droplet: 2.5 μL, time: 15 s, and the test value was the average of 10 tests and recorded in Table 1.

[0110] 4. Aging resistance: Samples with a thickness of 0.2 mm, a length of 2 cm and a width of 1 cm of the transparent high-temperature resistant cooling, heat dissipation and energy-saving self-cleaning film obtained in the embodiments and comparative examples were placed in a constant temperature and humidity chamber at 68±3°C and a relative humidity of 75±2%, and stored for 3 months. The samples were taken out after 3 months, and the tensile strength of the film layer was tested before and after 3 months (tested by the performance test 1 method), and the retention rate of tensile strength was calculated. Retention rate % = (tensile strength of the film layer after 3 months / tensile strength of the film layer before 3 months) × 100%. The test values ​​were taken as the average value of 10 tests and recorded in Table 1.

[0111] 5. Corrosion resistance: For the preparation method of a highly transparent, high-temperature resistant, cooling, heat dissipation, energy-saving and self-cleaning film obtained in the embodiments and comparative examples, a sample with a thickness of 0.2 mm, a length of 2 cm and a width of 1 cm was taken for a salt spray corrosion resistance test with 5 wt% NaCl. The sample was immersed in 5 wt% NaCl for 800 h. After the test, the sample was taken out to observe whether there was obvious film damage, tearing, corrosion oxidation and curling, and the tensile strength retention rate was tested again through the scheme in performance test 4. If there is no obvious phenomenon and the tensile strength retention rate is ≥85%, it is qualified, otherwise it is unqualified. The qualified rate results of 50 samples in each group are recorded in Table 1.

[0112] Table 1 Performance test results

[0113]

[0114]

[0115] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 8 in terms of mechanical properties, self-cleaning properties, waterproof properties and aging corrosion resistance. This is mainly due to the combined effect of the functional additives, composite nanoparticles and other matching technical solutions specified in the present application. Comparative examples 1 to 8 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests. This further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. A highly transparent, high temperature resistant, cooling, heat dissipation, energy-saving and self-cleaning film, characterized by: In parts by mass, the raw materials are: 15-45 parts of base emulsion, 25-65 parts of nanoparticles, 10-20 parts of functional additives, 20-30 parts of diluents, 2-3 parts of silicone oils, 1-3 parts of leveling agents, 2-5 parts of wetting agents, and 1-3 parts of dispersants; The base emulsion is a composition of modified acrylic emulsion, polyvinyl methyl ether and fluorocarbon emulsion; the mass ratio of the modified acrylic emulsion, polyvinyl methyl ether and fluorocarbon emulsion is (1.5-3): (0.5-1.2): (0.5-1.2); The nanoparticles are modified organic silicon nanosilver, nanographene, nanocerium sulfate, nanozirconium oxide, nanoaluminum oxide, nanozinc oxide, nanosilicon carbide, and nanotitanium dioxide in a mass ratio of (2-2.5): (0.1-18) (2-2.5): (1-1.4): (1-1.4): (1-1.4); (1~1.4):(1~1.4); The preparation method of modified organic silicon nanosilver comprises the following steps: S1: adding nanosilver to a mixed solvent of ethanol and isobutyl alcohol, uniformly dispersing it by ultrasonication at 200-250W, adjusting the pH value to 9-10 with triethanolamine, then adding tetraethyl orthosilicate, isopropyl alcohol, silane coupling agent and polysiloxane, heating to 65-70°C and keeping the temperature for reaction for 2.5-3h, and after the reaction is completed, centrifuging and filtering the product, washing with ethanol and drying it to obtain modified organic silicon nanosilver. The mass ratio of the modified organosilicon nanosilver, orthosilicic acid, ethyl isopropyl alcohol, silane coupling agent and polysiloxane is (20-30): (5-12) (6-8): (2-13): (1-1.4); The average particle size of the modified organosilicon nanosilver is 10 to 20 nm; The functional additive is a composition of polyethylene glycol methyl ether, epoxy block polyether and arylphenol polyoxyethylene ether; The functional additive is a composition of polyethylene glycol methyl ether, epoxy block polyether and arylphenol polyoxyethylene ether; The mass ratio of the polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether is (4-5): (3-3.5): (1-2).

2. A highly transparent, high temperature resistant, cooling, heat dissipation and energy-saving self-cleaning film according to claim 3, characterized in that: The average particle size of the modified organic silicon nanosilver is 10 to 20 nm.

3. The highly transparent, high temperature resistant, cooling, heat dissipating and energy-saving self-cleaning film according to claim 3 is characterized by: The average particle size of the nanographene is 10-20 nm.

4. The highly transparent, high temperature resistant, cooling, heat dissipating and energy-saving self-cleaning film according to claim 3, characterized in that: The average particle size of the nano zirconium oxide is 10-20 nm.

5. The highly transparent, high temperature resistant, cooling, heat dissipating and energy-saving self-cleaning film according to claim 3, characterized in that: The average particle size of the rice alumina is 10 to 20 nm.

6. The highly transparent, high temperature resistant, cooling, heat dissipating and energy-saving self-cleaning film according to claim 3, characterized in that: The average particle size of the nano zinc oxide is 10-20 nm.

7. The highly transparent, high temperature resistant, cooling, heat dissipating and energy-saving self-cleaning film according to claim 3, characterized in that: The average particle size of the nano-silicon carbide is 10-20 nm.

8. A method for preparing a highly transparent, high temperature resistant, cooling, heat dissipating, energy-saving and self-cleaning film according to any one of claims 1 to 8, characterized in that: The specific steps include the following steps: S1: Add diluent, functional additive, silicone oil and base emulsion into a high-speed mixer, and stir at 1200-1800 rpm for 10-20 minutes until uniform; S2: After adding the nanoparticles, continue to maintain a speed of 1200-1800 rpm and stir for 15-25 minutes; S3: Finally, add leveling agent, wetting agent and dispersant at a speed of 800-1000 rpm, stir for 8-10 minutes, and after completion, apply the mixture on the desired substrate surface, heat to 60-80°C and cure for 4-6 hours; or dry and cure for 24 hours; the result is obtained.

9. A highly transparent, high-temperature-resistant, cooling, heat-dissipating, energy-saving and self-cleaning film according to any one of claims 1 to 8 can maintain excellent high-temperature baking resistance, cooling and heat dissipation, self-cleaning performance and mechanical properties while maintaining good waterproof, aging resistance, corrosion resistance and anti-static properties, meeting the diverse performance requirements of the existing transportation, electronic products, industrial and civil fields for highly transparent, high-temperature-resistant, cooling, heat-dissipating, energy-saving and self-cleaning films, achieving good comprehensive performance and long service life, while having good energy-saving effects, reducing the cost of use, and having very excellent application prospects.

10. Where the patented invention is an innovative application of the best performance of various materials, products with similar performance can be produced by recombining the materials with the patented invention formula, without reducing the variety of materials or the content of materials, and are also protected by the patented invention and cannot be imitated.